Bioaugmentation combined with biochar to enhance thermophilic hydrogen production from sugarcane bagasse. (March 2022) - Huang, Jin-Rong; Chen, Xiong; Hu, Bin-Bin; Cheng, Jing-Rong; Zhu, Ming-Jun
Graphical abstract: Highlights: Maximum H2 production was boosted by 158.10% with bioaugmentation and biochar. Biochar significantly promoted degradation rate of SCB from 64.26% to 90.83%. Thermoanaerobacterium was further enriched with biochar to promote H2 production. Hydrogenase and electron transport system activities increased with biochar. Bioaugmentation and biochar expanded substrate utilization and improved H2 yield. Abstract: In this study, Thermoanaerobacterium thermosaccharolyticum MJ2 and biochar were used to enhance thermophilic hydrogen production from sugarcane bagasse. MJ2 bioaugmentation notably increased the hydrogen production by 95.31%, which was further significantly improved by 158.10% by adding biochar. The addition of biochar promoted the degradation of substrate, improved the activities of hydrogenase and electron transfer system, and stimulated microbial growth and metabolism. Microbial community analysis showed that the relative abundance of Thermoanaerobacterium was significantly increased by bioaugmentation and further enriched by biochar. PICRUSt analysis showed that MJ2 combined with biochar promoted metabolic pathways related to substrate degradation and microbial metabolism. This study provides a novel enhancement method for hydrogen production of the cellulolytic microbial consortium by exogenous hydrogen-producing microorganism combined with biochar and deepens the understanding of its functional mechanism.